1999
DOI: 10.1136/bmj.319.7209.537
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of Helicobacter pylori infection: population based study   Commentary: Helicobacter pylori---the story so far

Abstract: Objectives To assess the rate of intrafamilial transmission of Helicobacter pylori infection in the general population and the role of a family's social background. Design Population survey. Setting Campogalliano, a town in northern Italy with about 5000 residents. Participants 3289 residents, accounting for 416 families. Main outcome measures Prevalence of H pyloriinfection assessed by presence of IgG antibodies to H pylori. Results The overall prevalence of H pylori infection was 58%. Children belonging to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
2
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 39 publications
6
53
2
8
Order By: Relevance
“…*Nonresponders to eradication treatment. infection in our series is not higher than that (58%) in the general population of the area of Modena province, 36 or that (67%) in healthy Italian blood donors aged 50 years or older, 37 in keeping with the data from the other countries, where the prevalence of infection in patients with ITP is similar or lower than that of the general population of the same area, 6,10,13,38,39 with rare exceptions. 15,40 In our study, we observed a platelet improvement in 68% of patients with eradicated infection (60.5% of patients infected; 30.6% of total patients with ITP); in about 1500 patients so far reported in the literature, including the 3 US and Spanish cohorts with the lowest responses, the rate of response was about 53%.…”
Section: Discussionsupporting
confidence: 57%
“…*Nonresponders to eradication treatment. infection in our series is not higher than that (58%) in the general population of the area of Modena province, 36 or that (67%) in healthy Italian blood donors aged 50 years or older, 37 in keeping with the data from the other countries, where the prevalence of infection in patients with ITP is similar or lower than that of the general population of the same area, 6,10,13,38,39 with rare exceptions. 15,40 In our study, we observed a platelet improvement in 68% of patients with eradicated infection (60.5% of patients infected; 30.6% of total patients with ITP); in about 1500 patients so far reported in the literature, including the 3 US and Spanish cohorts with the lowest responses, the rate of response was about 53%.…”
Section: Discussionsupporting
confidence: 57%
“…The most accepted hypothesis is that the organism is transmitted through close personal contact and that the human being is the only significant reservoir of infection. 49 The detection of the bacterium in saliva, dental plaque, diarrheal stools, and vomit implicates oral-oral or fecal-oral transmission as possible routes of infection. Contaminated water and raw vegetables could be a source of H. pylori in the fecal-oral transmission pathway.…”
Section: Epidemiological Features Of the Infectionmentioning
confidence: 99%
“…El tamaño de muestra se determinó con la fórmula para comparar dos proporciones (28) -prevalencia intrafamiliar de 30 a 72,5% (10,22), un nivel de confianza de 95%, y un poder de 80%-resultando un total de 14 individuos por grupo.…”
Section: Población De Estudiounclassified
“…Se ha establecido la probabilidad de que la infección podría tener la ruta oral-oral o fecal-oral (10,11), sin embargo, no hay conclusiones de ello por la gran diversidad de factores tanto del huésped como del agente en las diferentes zonas del mundo y los grupos estudiados. La infección se adquiere con mayor frecuencia durante la niñez (1 a 5 años), persistiendo en forma crónica probablemente durante toda la vida de los individuos (12,13).…”
unclassified
See 1 more Smart Citation